Mild encephalopathy with a reversible splenial lesion in a girl with acute pyelonephritis - Jung Sook Yeom; Chung Mo Koo; Ji Sook Park; Ji-Hyun Seo; Eun Sil Park; Jae-Young Lim; Hyang-Ok Woo; Hee-Shang Youn (Korean Pediatric Society, 2018)
We report the case of a 12-year-old girl who had mild encephalopathy with a reversible splenial lesion (MERS) associated with acutepyelonephritis caused by Escherichia coli. The patient was admitted with a high fever, and she was diagnosed with acute pyelonephritis based on pyuria and the results of urine culture, which detected cefotaxime-sensitive E. coli. Although intravenous cefotaxime and tobramycin were administered, her fever persisted and her C-reactive protein level increased to 307 mg/L. On day 3 of admission, she demonstrated abnormal neuropsychiatric symptoms, such as delirium, ataxia, and word salad. Magnetic resonance imaging (MRI) of the brain performed on day 4 showed marked hyperintensities in the bilateral corpus callosum and deep white matter on diffusion-weighted images, with corresponding diffusion restriction on apparent diffusion coefficient mapping. No abnormalities or pathogens were detected in the cerebrospinal fluid; however, lipopolysaccharides (LPS, endotoxin) were detected in plasma (41.6 pg/mL), associated with acute neurological deterioration. Her clinical condition gradually improved, and no neurological abnormalities were observed on day 6. Follow-up brain MRI performed 2 weeks later showed near-disappearance of the previously noted hyperintense lesions. In this patient, we first proved endotoxemia in a setting of MERS. The release of LPS following antibiotic administration might be related to the development of MERS in this patient. The possibility of MERS should be considered in patients who present with acute pyelonephritis and demonstrate delirious behavior.